FUNCTIONAL PHYSICAL SCHEME OF THE INSTALLATION FOR THE GENERATION OF COMPRESSED AIR FOAM: Array - , О. Ф., А. І., О. М., С. А., С. М. (Municipal economy of cities. Series: «Economy science», 2018)
Compression air foam (CAF) is a low-frequency uniform fine-squeezed foam, obtained by mixing a foaming agent, water and compressed air or nitrogen This foam has a much higher efficiency compared to air-mechanical foam and water. The problem is that the issue of the optimal ratio of components in the CAF for the extinguishing of fires of various classes needs a scientific substantiation, which is not currently fully implemented. Such work requires theoretical and experimental confirmation. The most convenient tool for solving problems in describing stationary and transient processes in the design of constructions are modern software products, such as the Simulink simulation simulation environment (integrated into the MatLab software environment), which allows using separate blocks in the form of directed graphs to build dynamic models. In the article the functional-physical scheme of the installation for generating compression foam is proposed. It is proposed to create a mathematical model of the installation for generating a compression foam in such a way that it becomes an aggregation of separate units: a gas supply unit, a water mixing unit and a foam generator, a foam generator block and an outlet nozzle block, each of which is an autonomous mathematical model with its own the input and output, through which the interaction between the blocks is performed in the process of fulfilling the general task of mathematical modeling. These individual blocks can be modified according to changes in the design of the installation, leaving only the permanent outer shell (the number of inputs, outputs, dimensions) of the individual block. For the mathematical modeling of the proposed calculation blocks, the input and output parameters for each of them are identified, which is the basis for constructing a mathematical model of the installation for generating the compression foam. Keywords: functional-physical scheme, compressed air foam, mathematical model, functional block, input parameters, output parameters.